(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Water is prime natural resources fulfilling our needs in a precisious assets.we must acts to preserve and utilize every drop of water.water resources can be assessed on the basis of surface and subsurface water bodies.Climate change impact on ground Water the impact of climate change on ground water has been studied much less than the impact on surface waters. Ground water reacts to climate change mainly due to change in ground water recharge,but also change in river level in response to increase in mean Temperature,precipitation ,variability and sea level as mean precipitations.Changing land use pattern due to increasing ,urbanization, industrialization and agriculture activities are serious issues that causing increase ground water with drawal resulting in depletion of ground water resources and mining of ground water resources,along with deterioration of water quality.Rainfall is highly irregular and erratic and declining year to year due to change climatic conditions as result of serious deforestation global warming etc.Human health is affected by change in biodiversity and ecosystem.Climate change will affect the quality of drinking water and impact of fresh water availability and impact on public health. About 70% of Earth’s surface is water of which 97.5% is salty water and 2.5% is fresh water. Less than 1% of this 2.5% amount of freshwater is accessible. As sea water rise’s , salt water of ocean in filtrate as coastal fresh water due heavy rainfall and flooding waste more fertilizer and municipal sewage mixed with costal fresh water and change alter into more oxygen dead zone. Weather extreme and climate variability is main driver of food production in recent global challenge. Recent global challenge food security, fresh water availability, increase incidence of extreme high sea level. Loss of agriculture reproduction and increase in food prices and changes in weather patterns and alter availability and quality of water in many part of world. Climate change is an on-going phenomenon. This will inevitably bring about numerous environmental problems, including alterations to the hydrological cycle, which is already heavily influenced by anthropogenic activity.Chemical fertlizer’s has been adversely affecting the flora, fauna as well as soil quality . more ever every year plant pathogen are causing loss of 10 to 20% of agricultural production worldwide. Ground water will be vital to alleviate some of the worst drought situations. flooding and contaiminated water supplies, more intense weather events are likely to increase to risk of infectious disease epidemics and erosion of low-lying and costal land. Climate Chang will affect the quality of drinking Water and impact of fresh water availlablity and impact on public health it’s better to use UV Water purifiers.This paper will explore what climate change. Water is prime natural resources fulfilling our needs in a precisious assets.we must acts to preserve and utilize every drop of water.water resources can be assessed on the basis of surface and subsurface water bodies.Climate change imapact on ground Water the impact of climate change on ground water has been studied much less than the impact on surface waters. Ground water reacts to climate change mainly due to change in ground water recharge,but also change in river level in response to increase in mean Temperature,precipitation ,variability and sea level as mean precipitations.Changing land use pattern due to increasing ,urbanization, industrialization and agriculture activities are serious issues that causing increase ground water with drawal resulting in depletion of ground water resources and mining of ground water resources,along with deterioration of water quality.Rainfall is highly irregular and erratic and declining year to year due to change climatic conditions as result of serious global warming .Impacts of sea level rise on salinity intrusion global climate change has resulted in gradual sea level rise. sea level rise can cause saline water to migrate up stream in estuaries and rivers,thereby threating fresh water habitat and drinking- water supplies.Hydrology all the costal margin; fresh ground water flowing in land areas meets with saline ground water from the ocean. the fresh ground water flows from in land areas towards the coast where elevation and groundwater level are lower because salt water has higher content of dissolved salt and minerals. it denser the fresh water,causing it to have hydraulic head than freshwater. hydraulic head refers to the liquid pressure exerted by water column. the higher pressure density of salt water causes it to move into costal aquifiers in a a wedge shape under the freshwater. the salt water and fresh water meets in a transition zone where mixing occurs through dispersion and diffusion.